Competition Studies: Structuring Competencies in University Entrepreneurship Programs - Yu. V. Rubin; M. V. Lednev; D. P. Mozhzhukhin (Высшее образование в России, 2019)
. In this article, we introduce competition as an essential part of professional entrepreneurship activity and competition studies – as a significant direction in entrepreneurship education system. Competition competencies come into play at any stage of the entrepreneurship process. In this case, it is important to place competition competencies on relevant position within mainstream research in entrepreneurship education.The purpose of this article is to take a rational approach to defining, classifying competition competencies in entrepreneurship, and to structuring them as significant learning outcomes in entrepreneurship education in accordance with the types, kinds, methods, character, manners, styles of actor’s competition behavior, directions of competition management. Paper defines and describes categories of competition competencies.